Impact of corporate social responsibility disclosure on quality of health care institutions: Field study on Al-Kharj province , - Fateh Belouadah (Decision Science Letters)
This paper aims to investigate the commitment of health facilities in the Al-Kharj Province in Saudi Arabia to the dimensions of social responsibility and their disclosure impact on the improvement of the quality of health care. The study gains its importance from the importance of social responsibility which is one of the topics that contributes to the realization of the kingdom's Vision 2030. Partial Least Squares Structural Equation Modeling (PLS-SEM) is utilized in this study, to examine the relationship between dependent and independent variables. The study documents that the human dimension of social responsibility disclosure positively affects the quality of health care, while there is no clear effect of the legal dimension, the economic dimension, and the ethical dimension on the quality of health care institutions in Al-Kharj Province.